Lower cranial nerves MRI visualization - Chuvashova, O. Yu.; Gryazov, A. B.; Robak, K. O.; Bondarchuk, T. I. (Ukrainian Neurosurgical Journal, 2006)
40 patients research with different diseases but without lower cranial nerves damage were analyzed. The research was held on supply “Concerto” (Siemens, Germany) with magnetic field 0,2 Tl. TRUFFI program at slice height 0,8–1 mm in axial and coronal projections and next 3D image reconstruction let as to analyze lower cranial nerves and make them highly visible and to find the best diagnostics algorhythm.